To answer this question, the first step we need to do is solve the equation for x. Then, we have:
![y=-7x-4\Rightarrow y+4=-7x\Rightarrow x=((y+4))/(-7)\Rightarrow y=-((y+4))/(7)=(-y-4)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/2aicyk9o4ekh8z2vn4r3d0m60hk7zx32jq.png)
Then, changing y by x, we finally have that the inverse function is:
![f^(-1)(x)=(-x-4)/(7)](https://img.qammunity.org/2023/formulas/mathematics/college/la4llpcvp0w28drbbqoann99mmn71fsr78.png)
To check this result, if we have that x = 1 for the first equation, the value of y is:
![y=-7(1)-4=-7-4=-11](https://img.qammunity.org/2023/formulas/mathematics/college/w7vu7x59kj5ubhxpqu8smlqhnkyjd47p4d.png)
If we use this result in the inverse function, then we must have y = 1 ( that is the original value). That is
![f^(-1)(-11)=\text{ }(-(-11)-4)/(7)=(11-4)/(7)=(7)/(7)=1](https://img.qammunity.org/2023/formulas/mathematics/college/1sax16fews21v951g8zb4uytykm0p6rwvn.png)
Therefore, option 3 is the answer.